Mapping of Heterogeneous Catalyst Degradation in Polymer Electrolyte Fuel Cells. Issue 28 (8th June 2020) - Cheng, Lei; Khedekar, Kaustubh; Rezaei Talarposhti, Morteza; Perego, Andrea; Metzger, Michael; Kuppan, Saravanan; Stewart, Sarah; Atanassov, Plamen; Tamura, Nobumichi; Craig, Nathan; Zenyuk, Iryna V.; Johnston, Christina M.
Abstract: Pt catalysts in polymer electrolyte fuel cells degrade heterogeneously as the catalyst particles are exposed to local variations throughout the catalyst layer during operation. State‐of‐the‐art analytical techniques for studying degradation of Pt catalysts do not possess fine spatial resolution to elucidate such non‐uniform degradation behavior at a large electrode level. A new methodology is developed to spatially resolve and quantify the heterogeneous Pt catalyst degradation over a large area (several cm 2 ) of aged MEAs based on synchrotron X‐ray microdiffraction. PEFC single cells are aged using voltage cycling as an accelerated stress test and the degradation heterogeneity at a micrometer length scale is visualized by mapping Pt catalyst particle size after voltage cycling. It is demonstrated in detail that the Pt catalyst particle size growth is non‐uniform and follows the flow field geometry. The Pt particle size growth is greater in the area under the flow field land, while it is minimal in the area under the flow field channel. Additional non‐uniformity is observed with the Pt particle size increasing more rapidly at the air outlet area than the Pt particle size at the inlet area. Abstract : Synchrotron X‐ray microdiffraction mapping is adopted to visualize the heterogeneity of catalyst degradation in a polymer electrolyte fuel cell (PEFC). The map shows that degradation heterogeneity follows the flow field geometry with catalyst particles degrading faster under the land area. This provides a unique tool to study PEFC catalyst degradation, delivering new insights into the design and engineering of durable PEFCs.